PEMANTAUAN DAN MITIGASI TINGKAT POTENSI BENCANA KEKERINGAN DI KOTA DUMAI - Eggy Arya; Yuliana Safitri; Fitrah Andika Riyadhno (Jurnal Samudra Geografi, 2021)
Land drought that occurs during the dry season has a negative impact on vegetation, one of which is Peat soil is very sensitive to rising temperature causing forest fires. Dumai City is one of the areas that often experience forest and land fires, the effect of this fire makes the land has a declining quality including physics, chemistry, and the presence of soil erosion. In this paper, we monitor the increase and decline in several categories of land drought. The parameters used such as vegetation health index (VHI), vegetation condition index (VCI), and temperature condition index (TCI) in 2013 and 2018. The results of the study explain the drought area experienced a total increase during the observation period of 23.119 hectares of land, with the category without drought decreased by 23.119 ha, then the category of mild drought increased by 19.510 ha, then the category of drought was an increase of 13.444 ha, then the severe drought category decreased by 9.163 ha, and extreme drought decreased by 672 ha. this is in line with the increase in temperature in 2013 which reached 38 ºC and then increased to 47.53 º C in 2018 which is experiencing forest and land fires